2015
DOI: 10.1017/s0013091515000024
|View full text |Cite
|
Sign up to set email alerts
|

Smoothings of Fano Varieties With Normal Crossing Singularities

Abstract: This paper obtains criteria for a Fano variety X defined over an algebraically closed field of characteristic zero with normal crossing singularities to be smoothable. In particular, we show that X is smoothable by a flat deformation X → ∆ with smooth total space X if and only if T 1D is the singular locus of X.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…See [Hu06,4.3] for details of this construction. The fact that semistable degeneration of Fano manifolds is unique follows from [Tzi15]. The theorem is proved.…”
Section: Maximal Degenerationmentioning
confidence: 87%
See 2 more Smart Citations
“…See [Hu06,4.3] for details of this construction. The fact that semistable degeneration of Fano manifolds is unique follows from [Tzi15]. The theorem is proved.…”
Section: Maximal Degenerationmentioning
confidence: 87%
“…That is, X is unique up to isomorphism as an snc variety. From [Tzi15] it follows that this is equivalent to the claim that a maximal d-semistable snc Fano variety X = X i is unique.…”
Section: Maximal Degenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…1 where e 3 is the "central" (−1) curve on D 1 ≃ D 2 which is a del Pezzo surface of degree 7. Thus, by [Tz15] the simple normal crossing Fano variety F 1 ∪ F 2 can be smoothed in a semistable family.…”
Section: One Hasmentioning
confidence: 99%
“…In [Tz15] Tziolas showed that any d-semistable simple normal crossing Fano variety can be smoothed, that is, included as the special fiber in a semistable family. Hence, the classification of semistable degenerations of Fano varieties is equivalent to the classification of d-semistable simple normal crossing Fano varieties.…”
Section: Introductionmentioning
confidence: 99%